الأخطاء التحريرية لطلبة قسم الأدب العربي وتحليلها - Azman Ismail (Universitas Islam Negeri Ar-Raniry, 2014)
This article based on a study of writing errors contained in some thesis of Arabic Literature students of UIN Ar-Raniry Banda Aceh. Among the mistakes that often occur in the thesis is on writing Hamzah, morphology, grammar, and semantics. Several causes of these errors are: 1 ) The influence of mother tongue and the presence of the difference between Indonesian and Arabic in vocabulary, structure, and style of language; 2) Some errors occur on developmental stages of the students during process of Arabic language acquisition. So, there are some errors caused by lack of knowledge about the application of linguistic context in writing that comes from a thought, or the ignorance of rules of grammar.